Antimicrobial efficacy of silver, zinc oxide, and titanium dioxide nanoparticles incorporated in orthodontic bonding agent - Sarah Y Hailan; Mustafa M. Al-Khatieeb (College of Dentistry/ University of Baghdad, 2019)
Background: One of the most important complications of fixed orthodontic treatment is formation of white spots, which are initial carious lesions. Addition of antimicrobial agents into orthodontic adhesive material might be wise solution for prevention of white spots formation. The aim of this study was to evaluate the antibacterial properties of orthodontic adhesive primer against S. Mutans after adding the three different types of nanoparticles (Ag, ZnO, or TiO2). Materials and methods: Discs were prepared using empty insulin syringe approximately 2 mm×2 mm rounded in shape specimens (40 discs) were divided into four groups (ten discs for each group): The first group was the control (made from primer only), the second group (10 discs made from primer and incorporation of Ag NPs), the third group (10 discs made from primer and incorporation of ZnO NPs), and the fourth group (10 discs made from primer and incorporation of TiO2 NPs). The antibacterial properties of orthodontic bonding agent after incorporation of (Ag, ZnO, or TiO2) nanoparticles were evaluated by disc diffusion test and viable count of mutans streptococci. Results: The results of this study showed that there were high significant differences between the all groups using ANOVA F-test, and the colony forming unit were 99×10³, 39.6×10³, 19.4×10³, 6.6×10³ CFU/mL respectively. Conclusion: The incorporation of these nanoparticles (Ag, ZnO, or TiO2) into Transbond ™ XT adhesive primer helps to enhance the antibacterial properties of primer against the S. mutans.